JIHAD KONTEMPORER: Jihad Sebagai Jalan Kehidupan, Bukan Jalan Kematian - Ahmad Syafi'i; Suad Fikriawan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2020)
The purpose of this research is to try to reconstruct the discourse of Jihad as a way of life, not a way of death, as has so far been echoed by jihadist activists. This research concludes that jihad is one of the teachings of Islam. In fact, its position in religion ranks third after the practice of praying and serving one's parents. This shows how important every Muslim is in carrying out jihad. So the jihad that must be carried out in this contemporary era is more aimed at maintaining life (socio-economic sector), such as eradicating poverty and underdevelopment. For this reason, the meaning of jihad must always be contextualized according to the times. Because Islam is a religion that has the nature of shalih li kulli zaman wa makan.